Difference in the lipid nanoparticle technology employed in three approved siRNA (Patisiran) and mRNA (COVID-19 vaccine) drugs. (December 2021) - Suzuki, Yuta; Ishihara, Hiroshi
Abstract: Nucleic acid therapeutics are developing into precise medicines that can manipulate specific genes. However, the development of safe and effective delivery system for the target cells has remained a challenge. Lipid nanoparticles (LNPs) have provided a revolutionary delivery system that can ensure multiple clinical translation of RNA-based candidates. In 2018, Patisiran (Onpattro) was first approved as an LNP-based siRNA drug. In 2020, during the coronavirus disease 2019 (COVID-19) outbreak, LNPs have enabled the development of two SARS-CoV-2 mRNA vaccines, Tozinameran (Comirnaty or Pfizer-BioNTech COVID-19 vaccine) and Elasomeran (Spikevax or COVID-19 vaccine Moderna) for conditional approval. Here, we reviewed the state-of-the-art LNP technology employed in three approved drugs (one siRNA-based and two mRNA-based drugs) and discussed the differences in their mode of action, formulation design, and biodistribution.